Implementación de la tecnología emergente en maquinaria agrícola " - Terán Alvarado, Daniela Aracely (2024)
This document was developed based on the implementation of emerging technology in agricultural machinery. Emerging technologies are explored in detail because they transform modern agriculture. Among these technologies is precision agriculture, agricultural drones, artificial intelligence to the incorporation of electric or hybrid machinery, since it is considered an innovation and examined based on the revolution of traditional agricultural practices. Being able to identify which are the most up-to-date technologies and that producers have other alternatives to obtain positive results in the agricultural sector. These technologies are incorporated into agricultural machinery since they are practical tools that over time have had a significant impact on the agricultural sector. These machinery are autonomous because they are capable of carrying out the activities on their own thanks to the programs they have incorporated. in the software, due to this production costs are reduced in order to have sustainable agriculture. The impact that technology has caused today is favorable because it helps create modern agriculture, in order to improve productivity and obtain better results in the economic, productive and environmental fields through research strategies for the development of sustainable agriculture. The methodology carried out in the case study was a descriptive research and not experimental in nature, in order to achieve the expected objective which is to solve problems that arise in the agricultural sector.